Determinants of utilization of cryopreservation of germ cells in adolescent cancer patients in four European countries - Balcerek, Magdalena; Schilling, Ralph; Byrne, Julianne; Dirksen, Uta; Cario, Holger; Fernandez-Gonzalez, Marta Julia; Kepak, Tomas; Korte, Elisabeth; Kruseova, Jarmila; Kunstreich, Marina; Lackner, Herwig; Langer, Thorsten; et al. (European journal of pediatrics, 2020)
Infertility is a relevant late-effect following cancer treatment; yet, a large proportion of survivors cannot recall having been informed of this risk. In an intervention study, we examined if and how supportive patient information material on fertility/fertility-preserving measures influences utilization of cryopreservation in adolescent cancer patients. The control group, recruited 03/2014-01/2016, received the usual patient education at initial diagnosis. The intervention group, recruited 04/2016-10/2017, received patient education supported by a fertility flyer and brochure. Patients and parents were each asked questions on utilization of cryopreservation in a questionnaire 3 and 6 months after initial diagnosis. Patient core and therapy data were obtained from medical records. Overall, cryopreservation rates showed no significant difference between the control (32.7%, n = 37/113) and intervention group (36.6%, n = 37/101). In the control group, cryopreservation was associated with gender (OR 0.100, CI 0.023-0.427), age (OR 1.559, CI 1.077-2.258) and recalling information on fertility protection (OR 33.663, CI 2.100-539.574); in the intervention group, cryopreservation was related to gender (OR 0.093, CI 0.026-0.330) and the estimated infertility risk (OR 43.665, CI 2.157-883.974).Conclusion: Cryopreservation rates did not overall increase following the intervention; however, the individual risk seemed to be brought into attention more: Those at risk, including younger patients, cryopreserved at higher rates.What is Known:•Infertility is a relevant late-effect following adolescent cancer.•Guidelines recommend to offer fertility protection before cancer treatment.•A relevant proportion of adolescents with cancer are not aware of this risk.•Fertility protection seems under-used in cancer patients at risk for infertility.What is New:•Information material on fertility and protection in adolescents did not increase overall rates of cryopreservation.•Cryopreservation rates were improved according to individual risk for infertility.•Our flyers and brochures on fertility in cancer patients are available in various languages.
Keywords: Young Adult; Male; zárodečné buňky; Germ Cells; Neoplasms; mladý dospělý; zachování plodnosti; Cryopreservation; Adolescent; následné studie; Europe; Patient empowerment; mužské pohlaví; pacientův souhlas se zdravotní péčí; Fertility protection; mladiství; Follow-Up Studies; Patient Education as Topic; Evropa; vzdělávání pacientů jako téma; hodnocení výsledků zdravotní péče; lidé; Fertility impairment; ženské pohlaví; Patient education; Humans; Childhood and adolescent cancer; Risk; nádory; Outcome Assessment, Health Care; kryoprezervace; Female; riziko; Patient Acceptance of Health Care; Fertility Preservation